ICT Projects and Planning: From Equipments to Activities - Alves, Sónia Santos; Simões, Ana Paula; Gomes, Cristina Azevedo; Lima, Fernando Jorge (International Journal of Emerging Technologies in Learning (iJET), 2009)
Our study is based on a comparative analysis of two institutional documents, produced in public primary and secondary Portuguese schools, meant to enhance the use of ICT resources: an application to the Iniciativa Escolas, Professores e Computadores Portáteis (â??Schools, Teachers and Laptops Initiativeâ??), which aimed at equipping schools with ICT equipment, and the ICT Plan, a biannual plan of action for the integration of ICT in educational activities involving all the members of the educative community.The analysis focused on the typologies of activities planned for each school in both documents. As these documents were produced in consecutive school years, it was possible to recognize a continuity and evolution relationship towards the activation of ICT resources when conceiving, planning and developing learning activities.